TINJAUAN YURIDIS PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM TRANSAKSI JUAL BELI ONLINE - Febriana Natasya (The Juris, 2026)
The development of information technology has increased online buying and selling transactions in Indonesia. Online transactions provide convenience for consumers in obtaining goods and services quickly and efficiently. However, this development also creates various legal problems, especially regarding consumer protection. Consumers often experience losses due to goods that are not in accordance with descriptions, online fraud, delays in delivery, and misuse of personal data. This study aims to analyze legal protection for consumers in online transactions and dispute resolution arising from consumer losses in electronic transactions. This research uses normative legal research with statutory and conceptual approaches. The results show that consumer protection has been regulated in Law Number 8 of 1999 concerning Consumer Protection, Law Number 19 of 2016 concerning Electronic Information and Transactions, and Government Regulation Number 71 of 2019 concerning Electronic System and Transaction Operations. Dispute resolution can be carried out through litigation and non-litigation mechanisms. However, the implementation of consumer protection is still not optimal due to low public legal awareness and weak supervision of electronic commerce activities.